Computed Tomography Findings Suggestive of Connective Tissue Disease in the Setting of Usual Interstitial Pneumonia - Chung, Jonathan H; Montner, Steven M; Thirkateh, Prahasit; Cannon, Brenna; Barnett, Scott D; Nathan, Steven D (Journal of computer assisted tomography, 2021)
A usual interstitial pneumonia (UIP) pattern is common in idiopathic pulmonary fibrosis (IPF) and connective tissue disease-related interstitial lung disease (CTD-ILD). The purpose of the study was to validate imaging findings differentiating CTD-ILD from IPF in UIP. Patients with a multidisciplinary diagnosis of CTD-ILD or IPF and a UIP pattern on computed tomography and/or pathology were included in this study. Prevalence of 3 computed tomography findings shown to be associated with CTD-ILD (the straight edge sign [SES], the exuberant honeycombing sign, and the anterior upper lobe sign [AULS]) were tabulated in CTD-ILD and IPF subjects. The ability of each of these signs to discriminate between CTD-ILD and IPF was evaluated. Survival analysis was also performed using log-rank analysis. The study cohort included 50 CTD-ILD and 100 IPF subjects with UIP. The SES and the AULS were more common in CTD-ILD than IPF (prevalence, 36.0% and 34.9% in CTD-ILD vs 8.3% and 17.2% in IPF, respectively [P = 0.0105 - <0.001]). The highest specificity (95.7%) of CTD-ILD diagnosis was seen with bilateral SES. Moreover, the SES was associated with improved survival (P = 0.0383), which appeared to be largely because of improvement in survival in IPF subjects. The presence of AULS was associated with pulmonary functional abnormalities. A radiographic UIP pattern with evidence of SES or the AULS should raise suspicion for CTD-ILD rather than IPF. Patients with IPF and SES have an attenuated disease course and might represent a different phenotype than those without the SES.